MOBILITAS KELAS BARU DI DUNIA INDUSTRI PARIWISATA - Bambang Suharto, Janianton Damanik, M.Baiquni, dan Chafid Fandeli (Universitas Gadjah Mada, 2014)
The main study of this research solves the researchers empirically debate about the source of in justice inthe world tourism industry because of the class structure. First, the theory of post industrial related classshould look more human. The second, related theory of Marx saw class more regularly and degraded.This study used a mixed methods concurrent triangulation. Results of the analysis relationship betweenclasses show that there was a new class strengthened, namely the professional classes (54.5%) that havea high bargaining power against capital classes (1.5%) and the proletariats (44%). These conditionsreinforce the post industrial theory which shows that the system is open, technological advances, andspecifications facilitate mastery of the field of expertise towards a higher level of professionalism basedproclean care era cross borders and not consistent proletarianization process. This studies timated thetransformation of the proletariat in to a new class structures end to be stronger, in line with the directionof the professional class distributed double post status other than capitalist-professional worker as wellsmall to large scale.